Opinion of pharmacy interns of causes, consequences and prevention of dispensing errors in pharmacy - a qualitative study. - Natalia Wrzosek; Oliwia Dobbek; Joanna Awiżeń; Anna Kaliszewska; Dominika Polakowska-Lebiedzińska; Agnieszka Zimmermann (Polish Pharmaceutical Society, 2023)
License to practice the profession as a pharmacist in Poland has a person who has graduated at least five years of studies, including six months of traineeship in a pharmacy. Traineeship takes place in a pharmacy that has received positive opinions from the provincial pharmaceutical inspector and the district pharmacy self-government. A Student who realise traineeship performs tasks according to the professional practice program under the direct supervision of a supervisor. The professional activities that a student must learn as part of professional practice include dispensing medicinal products from a pharmacy. There is a risk of making a mistake. Errors made in a pharmacy may pose a risk to the health and life of patients, and may also have financial consequences. This work is an attempt to examine pharmacy practice in the area of drug dispensing safety. The main aim of the study is to assess pharmacy practice, attitudes and opinions of trainees on the causes, consequences and prevention of errors when dispensing medicinal products. The in-depth interview method was used. The studied group were sixth-year pharmacy students of the Medical University of Gdańsk undergoing a 6-month professional traineeship in generally available pharmacies. The interviews were conducted using a previously developed framework interview script. The interview recordings were listened to by at least 3 people each within a period not exceeding two weeks. Then, each interview was transcribed using the intelligent transcription model. The transcript of each interview was read by three researchers, who were students associated with the Pharmaceutical Law Student Scientific Club of MUG. Initial coding was performed into five categories created a priori. In the first stage, an in vivo coding technique was used, then a second coding cycle called "Pattern coding" was carried out. The interviews were anonymized when transcribing them. The study showed that the similarity of packaging and names is the main reason for errors during the shipment of medicines. The most common errors involve dispensing a different dose or form of the drug. High awareness of patients about their own pharmacotherapy increases its safety. Moreover, it was confirmed that the functionality of the e-prescription and the appropriate pharmacy program minimize errors during the expedition. Despite the implementation of various procedures and solutions aimed at increasing security, sometimes errors are detected with a delay or are ignored. Students doing traineeship in pharmacies complain about the lack of adequate preparation and support. The study showed that a six-month professional traineeship in a pharmacy, despite legal regulations, is an area that is insufficiently researched and insufficiently supervised in the student education process. The study showed that the similarity of packaging and names is the main reason for errors during the shipment of medicines. The most common errors involve dispensing a different dose or form of the drug High awareness of patients about their own pharmacotherapy increases its safety. Moreover, it was confirmed that the functionality of the e-prescription and the appropriate pharmacy program minimize errors during the expedition. Despite the implementation of various procedures and solutions aimed at increasing security, sometimes errors are detected with a delay or are ignored. Students doing internships in pharmacies complain about the lack of adequate preparation and support. The study showed that a six-month professional internship in a pharmacy, despite legal regulations, is an area that is insufficiently researched and insufficiently supervised in the student education process.